Availability of Antimalarial Drugs and Evaluation of the Attitude and Practices for the Treatment of Uncomplicated Malaria in Bangui, Central African Republic. (14th March 2010) - Manirakiza, Alexandre; Njuimo, Siméon Pierre; Le Faou, Alain; Malvy, Denis; Millet, Pascal
Abstract : National malaria management policy is based upon the availability of effective and affordable antimalarial drugs. This study was undertaken to evaluate the quality of the treatment of uncomplicated malaria cases in Bangui, an area with multidrug-resistant parasites, at a time preceding implementation of a new therapeutic policy relying on the artemisinin derivative combined treatment artemether-lumefantrine. A cross-sectional study was carried out in Bangui city to assess availability of antimalarial drugs and the performances of health workers in the management of uncomplicated malaria. Availability of drugs was recorded in all drugs wholesalers (n = 3 ), all pharmacies in health facilities (n = 14 ), private drugstores (n = 15 ), and in 60 non-official drug shops randomly chosen in the city. Despite a limited efficacy at the time of the survey, chloroquine remained widely available in the official and nonofficial markets. Artemisinin derivatives used in monotherapy or in combination were commonly sold. In health care facilities, 93% of the uncomplicated malaria cases were treated in the absence of any laboratory confirmation and the officially recommended treatment, amodiaquine-sulfadoxine/pyrimethamine, was seldom prescribed. Thus, the national guidelines for the treatment of uncomplicated malaria are not followed by health professionals in Bangui. Its use should be implemented while a control of importation of drug has to be reinforced.